Model Klasifikasi Berbasis Multiclass Classification dengan Kombinasi Indobert Embedding dan Long Short-Term Memory untuk Tweet Berbahasa Indonesia - Thariq Iskandar Zulkarnain Maulana Putra; Suprapto Suprapto; Arif Farhan Bukhori (Jurnal Ilmu Siber dan Teknologi Digital, 2022)
Purpose: This research aims to improve the performance of the text classification model from previous studies, by combining the IndoBERT pre-trained model with the Long Short-Term Memory (LSTM) architecture in classifying Indonesian-language tweets into several categories. Method: The classification text based on multiclass classification was used in this research, combined with pre-trained IndoBERT namely Long Short-Term Memory (LTSM). The dataset was taken using crawling method from API Twitter. Then, it will be compared with Word2Vec-LTSM and fined-tuned IndoBERT. Result: The IndoBERT-LSTM model with the best hyperparameter combination scenario (batch size of 16, learning rate of 2e-5, and using average pooling) managed to get an F1-score of 98.90% on the unmodified dataset (0.70% increase from the Word2Vec-LSTM model and 0.40% from the fine-tuned IndoBERT model) and 92.83% on the modified dataset (4.51% increase from the Word2Vec-LSTM model and 0.69% from the fine-tuned IndoBERT model). However, the improvement from the fine-tuned IndoBERT model is not very significant and the Word2Vec-LSTM model has a much faster total training time.